2012
DOI: 10.1021/cg201394y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Shape Engineering of Silicon Nanoparticles in a Thermal Aerosol Reactor

Abstract: In this work, the capability of gas phase synthesis for crystal shape engineering of silicon nanoparticles (SiNPs) in a hot wall reactor is demonstrated. Therefore, the necessary boundary conditions for the formation of monodisperse spherical SiNPs as well as octahedral-shaped particles from silane pyrolysis are systematically deduced. The different shapes of the SiNPs are ascribed to different growth regimes (reaction limitation, diffusion limitation) depending on the global process parameters. Single crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 48 publications
1
29
1
4
Order By: Relevance
“…Thec oncentration required to have supersaturation depends on the type of chemical reaction (e.g.t ype of precursor,d ecomposition kinetics) and on the synthesis conditions.W orking below the supersaturation limit produces few nuclei, that then may grow by heterogeneous growth. This trend opposes that observed by Kçrmer et al [59] which can be explained by the fact that the saturation limit was surpassed and therefore particle growth occurred by coalescence. Kçrmer and co-workers observed that asilane partial pressure inferior to 1mbar in 100 mbar of Ar allowed the production of Si objects larger than 100 nm.…”
Section: Precursor Concentrationcontrasting
confidence: 93%
See 2 more Smart Citations
“…Thec oncentration required to have supersaturation depends on the type of chemical reaction (e.g.t ype of precursor,d ecomposition kinetics) and on the synthesis conditions.W orking below the supersaturation limit produces few nuclei, that then may grow by heterogeneous growth. This trend opposes that observed by Kçrmer et al [59] which can be explained by the fact that the saturation limit was surpassed and therefore particle growth occurred by coalescence. Kçrmer and co-workers observed that asilane partial pressure inferior to 1mbar in 100 mbar of Ar allowed the production of Si objects larger than 100 nm.…”
Section: Precursor Concentrationcontrasting
confidence: 93%
“…[54,56,57] Thet emperature,t he total pressure in the reactor and the silane partial pressure are fundamental parameters,h aving ac onsiderable effect on the size,s ize dispersion, crystallinity [58] and even the shape of the produced particles. [59] Ostraat et al observed as ize increase from 6-7nmto40nmupon increasing the silane concentration from 10 ppb to 3300 ppb. [56] Kçrmer et al [58] investigated the effect of silane partial pressure (i.e.t he concentration) on the particle size:they observed an increase in the average size of Si particles from 25 to 40 nm by decreasing silane pressure from 1mbar to 0.5 mbar.The discrepancy in these two results arises from the particle growth mechanism, which proceeds through homogenous growth in the first case and heterogeneous growth in the latter.…”
Section: Aerosolmentioning
confidence: 95%
See 1 more Smart Citation
“…The mixing of the reactants and the carrier gas also adds flexibility to this system, with a variety of possible mixing arrangements. The better control of operating conditions allows the use of this system for the production of technological materials with tailored characteristics, such as highly crystalline silicon nanoparticles . However, to obtain monodisperse nanoparticles the use of low pressure (under 25 mbar) and low precursor concentration are required, leading to low throughput rates.…”
Section: Bottom‐up Processes For the Production Of Enmsmentioning
confidence: 99%
“…A completely differently shaped Si-NP formed by SiH 4 gas thermal dissociation at a high temperature (above 1100°C) has recently been reported19. The weakness of this approach is that it only leads to a few irregular crystalline nanoparticles immersed in a mess consisting of a large number of amorphous and polycrystalline particles and again inhibits the use of low cost substrates.…”
mentioning
confidence: 99%